Comparison of silica-based poly(amine) containing ion exchangers and their guanidine derivatives for selective PGM recovery from authentic refinery process solutions - Dhladhla, Nomasonto Ellen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.